Does a priming warm-up influence the incidence of V˙O2pl during a ramp test and verification phase? - JianBo Qiao; Paul Rosbrook; Daniel K. Sweet; Riana R. Pryor; David Hostler; David Looney; J. Luke Pryor (PLoS ONE, 2025)
Objective This study compared the effects of two different warm-up protocols (normal vs. priming) on the oxygen plateau (V˙O2pl) incidence rate during a ramp test. It also compared the cardiopulmonary responses during the ramp test and subsequent verification phase. Methods Eleven recreational cyclists performed two experimental visits. The first visit required a normal warm-up (cycling at 50 W for 10 min) followed by the ramp test (30 W.min-1) and supramaximal verification phase with 30 min rest between tests. The second visit required a priming warm-up (cycling at 50 W for 4 min increasing to 70% difference between the gas exchange threshold [GET] and maximum work rate [WRmax] for 6 min) followed by the same protocol as in the first visit. Physiological responses were collected during the exercise and compared. Oxygen kinetics (V˙O2 Kinetics) and V˙O2pl incidence rate were determined during the ramp tests for both visits. Results As planned, following the warm-up the priming visit experienced greater physiological response. However, the incidence rate of V˙O2pl during the ramp test was the same between visits (73%), and maximal oxygen uptake was not different between visits after the ramp test (normal, 4.0 ± 0.8; primed, 4.0 ± 0.7 L·min−1, p = 0.230) and verification phase (normal, 3.8 ± 0.6; primed, 3.8 ± 0.7 L·min−1, p = 0.924) using a Holm-Bonferroni correction for controlling family-wise error rate. V˙O2 Kinetics were not different between visits during the ramp test (normal, 10.8 ± 1.1; primed, 10.8 ± 1.2 mL·min−1·W-1, p = 0.407). The verification phase confirmed V˙O2max in 100% for both the normal and priming visits. Conclusion Our hypothesis that a priming warm-up facilitates the incidence rate of V˙O2pl during a ramp test is not supported by the results. The verification phase remains a prudent option when determining a ‘true’ V˙O2max is required.